2021
DOI: 10.4081/ejtm.2021.10063
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity in Ardabil, North West of Iran: Prevalence and risk factors

Abstract: Retinopathy of prematurity (ROP), which affects the retina of premature infants, is a leading cause of blindness in premature infants worldwide. The aim of this study was to evaluate the frequency and risk factors of retinopathy of prematurity infants referred to Alavi hospital between October 2018 and October 2019. In the present study, 400 infants with gestational age less than 34 weeks and or birth weight of 2000 g or less were enrolled in the study. Required information including sex, gestational age, mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…In the present study, 526 infants were screened and showed an institutional incidence of ROP of 24.9% (131 out of 526 infants) and Zone I ROP of 9.5% (50 infants). Much lower incidences of 1.8% and 3.7% were reported by Braimah et al [9] (Ghana) and Fekri et al [10] (Iran). The wide variation between the incidence of Zone I ROP between the present study and other Western studies is attributable to the variation in the sample size of the studies and In our study, we found that out of 97 eyes, a total of 33 (34.02%) eyes show spontaneous regression all of them belong to stages 1 and Hence, a proper timely follow-up is also important in these patients, we cannot exclude the probability of ROP based on the first examination, because when they are present, they are very preterm so vascularization is only until Zone I.…”
Section: Discussionmentioning
confidence: 71%
“…In the present study, 526 infants were screened and showed an institutional incidence of ROP of 24.9% (131 out of 526 infants) and Zone I ROP of 9.5% (50 infants). Much lower incidences of 1.8% and 3.7% were reported by Braimah et al [9] (Ghana) and Fekri et al [10] (Iran). The wide variation between the incidence of Zone I ROP between the present study and other Western studies is attributable to the variation in the sample size of the studies and In our study, we found that out of 97 eyes, a total of 33 (34.02%) eyes show spontaneous regression all of them belong to stages 1 and Hence, a proper timely follow-up is also important in these patients, we cannot exclude the probability of ROP based on the first examination, because when they are present, they are very preterm so vascularization is only until Zone I.…”
Section: Discussionmentioning
confidence: 71%
“…One of the most significant and curable causes of childhood blindness is retinopathy of prematurity (ROP), a proliferative retinopathy that damages retinal blood vessels in preterm and low-birth-weight infants. 1 Retinal detachment, which results from scarring of aberrant retinal blood vessels, is the primary cause of visual impairment and blindness in patients with ROP. 2 Initially, it was speculated that ROP development was related to the complex and unreported use of oxygen supplementation in the care of premature infants placed in closed incubators for the treatment of respiratory distress.…”
Section: Introductionmentioning
confidence: 99%
“…However, because some studies believe that this condition is dependent on geographic and medical facilities, the causal association between these elements has not been definitively proven. 1 The immature vasculature develops in two stages. First, ischemia and a hyperoxic phase restrict the blood vessels in the retina.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations